The effect of music streaming platforms algorithms on taste and social distinction: do recommendation algorithms serve us or define us? - Randriamahefa-Barnouin, Camille Adrienne Jeannette (2024)
This paper discusses the impact of algorithms on the musical taste of French digital natives (individuals between 18 and 30 years old) listening to music on streaming platforms. We try to understand through what means music preferences may become homogeneous, and the impact of this homogenization on the sense of self and the practice of social distinction on a daily basis. The analysis is based on 16 structured interviews enriched by already existing literature. We show that there has been a drastic shift in music consumption in the streaming platform and algorithmic age. This change affects the relationship between the public and the artist and leads to a kind of superficiality which diminish the opportunity for social distinction through music. This paper contributes to the literature of taste and social distinction as it demonstrates that musical taste is shaped differently in the advent of streaming platforms since they modify greatly the way music is produced and consumed thus impacting the way music listeners can use music as a social distinction tool.